- TANTRAISME : MENGKONSTRUKSI KESADARAN TRANSENDENTAL MELALUI RITUAL INTIM EROTIS: - - Redi, I Wayan; Saputra, I Made Gede Nesa (Sphatika: Jurnal Teologi, 2025)
The phenomenon of sexual deviation is rampant as a form of refinement of the occurrence of various immoral cases in the world. In fact, the phenomenon of sexual deviation often occurs in environments or institutions that are labeled as religious. This happens because of the cult of taboo terms in sexuality which until now has been understood by humanity collectively. This indicates that there has been a polarization of thought that has occurred since ancient times, which distinguishes the corridors of spirituality and sexuality in a thick barrier. In this case, sexuality becomes something that is destructive and has negative connotations. Likewise with Tantra, which is always given negative connotations because its teachings contain sexual concepts as a form of ritual. To obtain valid and comprehensive data, this paper uses a qualitative method with a descriptive approach, meaning that this research is carried out by analyzing and describing various data obtained through the collection of data that has been collected, then synthesizing the data, namely through the process of sorting and selecting various relevant data so as to be able to produce an accurate research synthesis. In its development, Tantra is viewed in two conflicting paradigms, so it needs to be studied in the dialectic of thought, because Tantra is a teaching that has gone global, and the term Tantra has become familiar in human development socially. In this paper, a holistic understanding of Tantra is presented as a medium for constructing transcendental consciousness through erotic rituals. In the view of Tantra, sexuality is one of the efforts to achieve freedom because the teachings of Tantra are not only defined as limited to sexual or biological activities, but there are divine values ​​in them. As a factual form, Tantra spirituality is the compounding of the elements of kama petak and kama bang into Kama Dewa (Ongkara), which in the semiotic view is understood as a state of God that is full of tranquility and without attachment to the elements of awidya.